Synthesis and characterize the antioxidant activities of chalcone derivatives / 'Insyirah Iskandar Zulkarnain - Iskandar Zulkarnain, 'Insyirah (2024)
Chalcones are a group of natural compounds that have attracted much attention because of their varied pharmacological characteristics. The synthesis, and antioxidant properties of chalcones and their derivatives are the main subjects of this study. Four chalcone derivatives were synthesized by Claisen-Schmidt condensation of suitable aromatic ketones or substituted aromatic ketones with benzaldehydes or substituted benzaldehydes. They were four derivatives of chalcones, namely 2-hydroxy-4’-bromochalcone, 2-hydroxy-4’-chlorochalcone, 4’-bromochalcone and 4’-chlorochalcone. Purification of the synthesized chemicals was achieved using recrystallization and column chromatography. The determination of the structure of synthesized compounds were done by its physical properties like melting point and TLC followed by spectroscopic analysis such as NMR and FTIR. The antioxidant capacity of synthesized chalcones was assessed. The results showed significant antioxidant activity, indicating that chalcones may be useful as naturally occurring antioxidants. Overall, this work emphasizes the synthesis, and antioxidant properties of chalcones, highlighting their potential for use in medicine and other therapeutic fields. Additional investigation into chalcone derivatives might result in the creation of innovative medications with improved effectiveness and fewer adverse effects.